Reptiles of Costa Rica : A Field Guide - Leenders, Twan (Book collections on Project MUSE., 2019)
"Field guide to the crocodilians, turtles, lizards, and snakes of Costa Rica. Species accounts include photographs, range maps, key characteristics, conservation status, and information about distribution, habitats, natural history, and similar species that might cause confusion in the field"--